Information uncertainties and asset pricing puzzles: risk or mispricing?. Issue 12 (7th December 2015) - Li, Keming; Uddin, Mohammad Riaz; Diltz, J. David
Abstract : Purpose: – Prior research has documented the role of information uncertainty in the cross-sectional variation in stock returns. Miller (1977) hypothesizes that if information uncertainty is caused by differences of opinion, prices will reflect only the positive beliefs due to short-sale constraints. These anomalous stock price behaviors may result from mispricing. In contrast, Merton (1974) asserts that default risk is a function of the uncertainty in the asset value process. Information uncertainty may be subsumed by credit or default risk. The paper aims to discuss these issues. Design/methodology/approach: – The authors employ various sorting techniques and Fama-MacBeth Regressions to test the hypotheses. Findings: – The authors provide empirical evidence consistent with Merton's (1974) default risk hypothesis and inconsistent with Miller's (1977) mispricing hypothesis. Research limitations/implications: – Risk aversion and not misplacing is the primary factor driving information-related anomalies in equities markets. Practical implications: – It would be quite difficult to find arbitrage opportunities in equities markets because there appears to be little, if any, mis-pricing due to information uncertainties. Originality/value: – This study provides important information about the primary underlying information-related source of certain empirical anomalies in the cross-section of stock returns.